Inosine triphosphate pyrophosphatase polymorphisms are predictors of anemia in Chinese patients with chronic hepatitis C during therapy with ribavirin and interferon. Issue 1 (23rd August 2019) - Chi, Xiumei; Wang, Moli; Pan, Yu; Jiang, Jing; Jiang, Tao; Yan, Hongqing; Wu, Ruihong; Wang, Xiaomei; Gao, Xiuzhu; Niu, Junqi
Abstract: Background and Aim: Polymorphisms of inosine triphosphate pyrophosphatase (rs1127354 and rs6051702) and interferon lambda 4 (IFLN4) (rs12979860) are indicators of anemia and/or sustained virological response (SVR) in patients with chronic hepatitis C on ribavirin/interferon. The study aims to investigate the associations of rs1127354, rs6051702, and rs12979860 with hemoglobin levels and SVR in patients on ribavirin/interferon. Methods: Polymorphisms were detected by pyrosequencing. Levels of hemoglobin and hepatitis C virus (HCV) RNA were measured at weeks 2, 4, 12, 24, 36, 48, and 72 of treatment. Results: A total of 351 patients (median age, 50 years; male, 71.2%) were recruited and had HCV genotypes 1b (55.8%) or 2a (37.0%). Vedian baseline hemoglobin and HCV RNA were 155 g/dL and 6.07 log10 IU/mL. Major allele homozygosity was observed in 76.3% for rs1127354 (CC), 70.9% for rs6051702 (AA), and 89.7% for rs12979860 (CC). At 4 weeks of ribavirin/interferon treatment, a more significant reduction in hemoglobin was observed with rs112754 CC than with AC/AA ( P < 0.05). A decline ≥3 g/dL was more common in patients with the rs112754 CC than with the other two polymorphisms. No significant change was observed regarding rs6051702 and rs12979860 variants. In the multivariable analysis, rs1127354 AA/AC ( vs CC) were independently associated with lower odds of hemoglobin decline of > 3 g/dL at 4 weeks (odds ratio, 0.21; 95% CI, 0.09–0.46; P < 0.0001). In 258 patients with 72‐week outcome data available, rs1127354, rs6051702, and rs12979860 were not associated with SVR (all P > 0.05). Conclusion: rs1127354 polymorphisms are associated with hemoglobin levels in Chinese patients with chronic hepatitis C treated with ribavirin/interferon.